2D Raman band splitting in graphene: Charge screening and lifting of the K-point Kohn anomaly. Issue 1 (December 2017) - Wang, Xuanye; Christopher, Jason; Swan, Anna
Abstract Pristine graphene encapsulated in hexagonal boron nitride has transport properties rivalling suspended graphene, while being protected from contamination and mechanical damage. For high quality devices, it is important to avoid and monitor accidental doping and charge fluctuations. The 2D Raman double peak in intrinsic graphene can be used to optically determine charge density, with decreasing peak split corresponding to increasing charge density. We find strong correlations between the2D 1 and 2D 2 split vs 2D line widths, intensities, and peak positions. Charge density fluctuations can be measured with orders of magnitude higher precision than previously accomplished using the G-band shift with charge. The two 2D intrinsic peaks can be associated with the "inner" and "outer" Raman scattering processes, with the counterintuitive assignment of the phonon closer to theK point in theKM direction (outer process) as the higher energy peak. Even low charge screening lifts the phonon Kohn anomaly near theK point for graphene encapsulated in hBN, and shifts the dominant intensity from the lower to the higher energy peak.